2020
DOI: 10.1088/1361-6463/ab795b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic aspects of plasma-enhanced catalytic methane decomposition by time-resolved operando diffuse reflectance infrared Fourier transform spectroscopy

Abstract: To study mechanistic aspects of plasma-enhanced catalysis, methane is decomposed by a supported Ni catalyst assisted by an Ar/O2 atmospheric pressure plasma jet (APPJ). The time-resolved surface response of the Ni catalyst is investigated by operando diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) using various experimental settings. Catalyst temperatures of room temperature and 500 °C and nozzle-catalyst surface distances of 3, 5 and 8 mm were examined, and the amount of O2 of the Ar/O2 g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
35
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…The authors found that treatment with Ar plasma resulted in the formation of surface-bound CO, which was oxidized to CO 2 upon admixing of O 2 to the plasma. These results indicate that the CO selectivity can be altered by adjusting the flow of O 2 . Gibson et al investigated CH 4 oxidation using a Pd/Al 2 O 3 catalyst in a plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found that treatment with Ar plasma resulted in the formation of surface-bound CO, which was oxidized to CO 2 upon admixing of O 2 to the plasma. These results indicate that the CO selectivity can be altered by adjusting the flow of O 2 . Gibson et al investigated CH 4 oxidation using a Pd/Al 2 O 3 catalyst in a plasma.…”
Section: Introductionmentioning
confidence: 99%
“…However, they also suggested the presence of carboxylate groups or COO – , which are likely precursors to CO 2 . Zhang et al investigated the decomposition and oxidation of CH 4 exposed to a Ni catalyst on an Al 2 O 3 /SiO 2 support and an Ar or Ar/O 2 APPJ using time-resolved DRIFTS. The authors found that treatment with Ar plasma resulted in the formation of surface-bound CO, which was oxidized to CO 2 upon admixing of O 2 to the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Infrared (IR) spectroscopy has been one of the prominent analytical techniques to study surface science in thermal catalysis research but has only recently began to make inroads in plasma catalysis research. To date, there have been a few studies using in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) and transmission IR spectroscopy to study plasma–catalyst coupling. These studies highlight the possibility of using IR spectroscopy to understand the reaction pathways in plasma catalysis.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is desirable to utilize surface-specific IR techniques in conjunction with plasma-phase characterization to better understand the fundamental interactions of the plasma with a surface. Finally, the majority of the in situ/operando IR spectroscopy techniques reported to date have focused on probing surface and gas-phase products without simultaneously characterizing the plasma-phase. To the best of our knowledge, there has been no report on a spectroscopic tool that can study surface-adsorbed species, gas-phase products, and plasma characteristics simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…Most notably, the microscopic plasma-induced phenomena at the catalyst surface remain elusive, as well as their potential impact on the activity of the catalyst [9]. Only very recently, experimental methods have been devised to access in situ insights on the surface processes and intermediates in plasma-catalytic setups [10,11].…”
Section: Introductionmentioning
confidence: 99%